Minimum Common Difference

Algebra Level 3

Three unequal positive integers are in an arithmetic progression , whose common difference is a perfect square. The difference between the squares of the largest number and the second largest number equals the cube of the smallest number. What is the minimum value of the common difference?

Bonus: Is there any other such common difference which is a perfect square?


The answer is 49.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chris Lewis
Sep 2, 2020

Say the three numbers are a , a + d 2 , a + 2 d 2 a,a+d^2,a+2d^2

with both a , d a,d positive integers.

Then the question asks for the smallest value of d 2 d^2 (the common difference) such that ( a + 2 d 2 ) 2 ( a + d 2 ) 2 = a 3 \left(a+2d^2\right)^2-\left(a+d^2\right)^2=a^3

Tidying the left hand side, d 2 ( 2 a + 3 d 2 ) = a 3 d^2 \left(2a+3d^2\right)=a^3

Now, let a = k d a=kd (note that k k may not be an integer, but is certainly rational).

The equation becomes d 2 ( 2 k d + 3 d 2 ) = k 3 d 3 d^2 \left(2kd+3d^2\right)=k^3 d^3

Cancelling, k 3 2 k 3 d = 0 k^3-2k-3d=0

Now, this is a monic polynomial in k k with integer coefficients. By the integral root theorem, k k is either irrational or an integer. We know it's not irrational, by definition, so it must be an integer.

Hence d = k 3 2 k 3 d=\frac{k^3-2k}{3} for some integer k k .

Since k 3 2 k = k ( k 2 2 ) k^3-2k=k(k^2-2) and k 2 2 ≢ 0 ( m o d 3 ) k^2-2 \not\equiv 0 \pmod 3 , we need k k to be a multiple of 3 3 ; take k = 3 t k=3t .

So all solutions have the form d = 9 t 3 2 t d=9t^3-2t , a = 3 t d a=3td .

The smallest of these comes from t = 1 t=1 , giving d = 7 d=7 , a = 21 a=21 . The three terms of the sequence are 21 , 70 , 119 21,70,119 with a common difference of 49 \boxed{49} .

What happened to your report? :)

A Former Brilliant Member - 9 months, 1 week ago

Log in to reply

:) deleted as soon as I saw I had solved the wrong problem!! I got lucky that the integral root idea still worked here.

Chris Lewis - 9 months, 1 week ago

Let the smallest number in the arithmetic progression be a a and the common difference be d d . Then we have:

( a + 2 d ) 2 ( a + d ) 2 = a 3 ( a + 2 d + a + d ) ( a + 2 d a d ) = a 3 ( 2 a + 3 d ) d = a 3 3 d 2 + 2 a d a 3 = 0 \begin{aligned} (a+2d)^2 - (a+d)^2 & = a^3 \\ (a+2d+a+d)(a+2d-a-d) & = a^3 \\ (2a+3d)d & = a^3 \\ 3d^2 + 2ad - a^3 & = 0 \end{aligned}

d = 2 a + 4 a 2 + 12 a 3 6 = a ( 1 + 3 a 1 ) 3 \begin{aligned} \implies d & = \frac {-2a + \sqrt{4a^2+12a^3}}6 = \frac {a(\sqrt{1+3a}-1)}3 \end{aligned}

For d d to be an integer, 1 + 3 a 1+3a must be a perfect square. Let b 2 = 1 + 3 a b^2 = 1+3a . Then we have:

d = a ( b 1 ) 3 Note that a = b 2 1 3 = ( b 2 1 ) ( b 1 ) 9 = ( b 1 ) 2 ( b + 1 ) 9 \begin{aligned} d & = \frac {a(b-1)}3 & \small \blue{\text{Note that }a = \frac {b^2-1}3} \\ & = \frac {(b^2-1)(b-1)}9 \\ & = \frac {(b-1)^2(b+1)}9 \end{aligned}

Now we note that d d is a perfect square when b + 1 9 \dfrac {b+1}9 is a perfect square. Bonus: That is d d is a perfect square whenever b + 1 = 9 n 2 b+1 = 9n^2 , where n n is a positive integer. And the smallest perfect square d d is when n = 1 n=1 or b = 8 b=8 , d = ( 8 1 ) 2 ( 8 + 1 ) 9 = 7 2 = 49 \implies d = \dfrac {(8-1)^2\cancel{(8+1)}}{\cancel 9} = 7^2 = \boxed{49} .

Pop Wong
Sep 1, 2020

Let the sequence be a , a + d 2 , a + 2 d 2 a, a+d^2, a + 2d^2

( a + 2 d 2 ) 2 ( a + d 2 ) 2 = a 3 ( 2 a + 3 d 2 ) ( d 2 ) = a 3 3 ( d 2 ) 2 + 2 a ( d 2 ) a 3 = 0 d 2 = 2 a + 4 a 2 + 12 a 3 6 neglect -ve = 2 a + 2 a 1 + 3 a 6 = a + a 1 + 3 a 3 as ( 3 q + 2 ) 2 = 3 Q + 1 for some integer q, Q, the numerator will be a + a ( 3 Q + 2 ) = ( 3 Q + 1 ) a a = 3 k = ( 3 k ) + ( 3 k ) 1 + 3 ( 3 k ) 3 = k + k 1 + 9 k as ( 9 m ± 1 ) 2 = 9 k + 1 for some integer m, 1 + 9 k = ( 9 m ± 1 ) [1] d 2 = { 9 m k ( 9 m 2 ) k By [1] ( 9 m ± 1 ) 2 = 9 k + 1 9 k = ( 9 m ± 1 ) 2 1 = { ( 9 m + 2 ) ( 9 m ) ( 9 m ) ( 9 m 2 ) k = { ( 9 m + 2 ) ( m ) ( 9 m 2 ) ( m ) d 2 = { 9 m 2 ( 9 m + 2 ) = 3 2 m 2 ( 9 m + 2 ) case 1 ( 9 m 2 ) 2 ( m ) = ( 9 m 2 ) 2 ( m ) case 2 \begin{aligned} (a+2d^2)^2 - (a+d^2)^2 &= a^3 \\ (2a+3d^2) (d^2) &= a^3 \\ 3(d^2)^2 + 2a (d^2) - a^3 &= 0\\ d^2 &= \cfrac{-2a + \sqrt{ 4a^2 + 12 a^3}}{6} \hspace{5mm} \color{#3D99F6}{\text{neglect -ve } }\\ &=\cfrac{-2a + 2a\sqrt{ 1 + 3 a}}{6} \\ &= \cfrac{-a + a\sqrt{ 1 + 3 a}}{3} \\ \text{ as }\textcolor{#3D99F6}{ (3q+2)^2 = 3Q + 1 } &\text{ for some integer q, Q, the numerator will be } -a + a(3Q+2) = (3Q+1) a \rightarrow \boxed{a=3k} \\ &= \cfrac{-(3k) + (3k)\sqrt{ 1 + 3(3k)}}{3} \\ &=-k+k\sqrt{1+9k}\\ \text{ as }\textcolor{#3D99F6}{ (9m \pm 1)^2 = 9k + 1 } &\text{ for some integer m, } \sqrt{1+9k} = (9m \pm 1) \hspace{5mm} \text{[1]}\\ \therefore d^2 &= \left\{\begin{array}{c}&9mk \\ & (9m-2)k \end{array} \right. \\ \text{ By [1] } (9m \pm 1)^2 &= 9k + 1 \implies 9k =(9m \pm 1)^2 - 1 =\left\{\begin{array}{c}&(9m+2)(9m) \\ &(9m) (9m-2) \\ \end{array} \right. \\ \implies k &= \left\{\begin{array}{c}&(9m+2)(m) \\ &(9m-2)(m) \\ \end{array} \right. \\ \implies d^2 &= \left\{\begin{array}{c}&9m^2(9m+2) = 3^2 m^2 (9m+2) \hspace{5mm} \text{case 1} \\ &(9m-2)^2(m) = (9m-2)^2 (m) \hspace{5mm} \text{case 2} \\ \end{array} \right. \\ \end{aligned}

For case 1, we need 9 m + 2 = x 2 9m+2 = x^2 for some integer x , x,

there is no solution as ( 3 m ) 2 = 9 m 2 , ( 3 m ± 1 ) 2 = 9 m 2 ± 6 m + 1 6 m + 1 = 9 Q + 2 6 m = 9 Q + 1 0 1 ( m o d 3 ) ! (3m)^2 = 9m^2, (3m\pm 1)^2 = 9m^2 \pm 6m+1 \Rightarrow 6m+1=9Q+2 \Rightarrow 6m = 9Q + 1 \Rightarrow 0 \equiv 1 \pmod 3 !

For case 2, we need m = x 2 m = x^2 , there are infinite many solutions.

d 2 = ( 9 x 2 2 ) 2 ( x 2 ) \therefore d^2 = (9x^2-2)^2 (x^2) for integer x , a = 3 k = 3 ( 9 x 2 2 ) ( x 2 ) min . d 2 = ( 9 2 ) 2 ( 1 ) = 7 2 = 49 x, a = 3k = 3 (9x^2-2)(x^2) \\ \min. d^2 = (9-2)^2 (1) = 7^2 = \boxed{49} while a = 3 ( 9 2 ) ( 1 ) = 21 a = 3(9-2)(1) = 21

The next d 2 = ( 9 ( 2 ) 2 2 ) 2 ( 2 2 ) = 3 4 2 2 2 = 6 8 2 = 4624 , a = 3 ( 9 × 4 2 ) × 4 = 408 d^2 = (9(2)^2-2)^2 (2^2) = 34^2 \cdot 2^2 = 68^2 = 4624, a=3(9\times4-2)\times4 = 408


9 k + 1 = ( 3 m ± 1 ) 2 9 k + 1 = 9 m 2 ± 6 m + 1 9 k = 9 m 2 ± 6 m m = 3 M , set 9 k + 1 = ( 9 m ± 1 ) 2 9k+1 = (3m\pm 1)^2 \implies 9k+1 = 9m^2 \pm 6m + 1 \implies 9k = 9m^2 \pm 6m \implies m = 3M, \therefore \text{ set } 9k+1 = (9m\pm 1)^2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...